Pengelolaan Bank Sampah Bersama Masyarakat Membuat Ecoenzym Di Desa Sidamukti - Firdayetti Firdayetti; Sumiyarti Sumiyarti; Rakendro Rakendro; Ida Busnety; Farah Nur Azizah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Waste bank management is an important innovation in efforts to maintain environmental sustainability. One approach that is increasingly developing is the application of ecoenzymes in managing waste banks together with the community. Ecoenzymes, as natural bioactivators, have a significant role in accelerating the decomposition process of organic waste, reducing waste and improving compost quality. This research was carried out in the coastal area, Sidamukti Village, Sukaresmi District on February 14 2024. This research aims to evaluate the benefits of ecoenzymes in managing waste banks in collaboration with the community. Participatory/field methods are used to involve activities with the community in the process of collecting, separating and managing waste. The research results show that the application of ecoenzymes can increase composting efficiency, reduce carbon footprints, and provide unique works of art from waste management that have economic value. In addition, collaboration with the community involves them actively in the waste management process, increases environmental awareness, and creates a positive impact on environmental cleanliness. Therefore, the implementation of ecoenzymes in managing waste banks with the community provides great ecological and social benefits, supports efforts to maintain environmental sustainability and improves the quality of life of the community.